2021
DOI: 10.32598/ahs.10.4.314.1
|View full text |Cite
|
Sign up to set email alerts
|

Human Health Risk of Some Heavy Metals Accumulated in Tomatoe, Cucumber, Potato, and Onion Grown in Dezful and Shushtar

Abstract: Background & Aims of the Study: This study aimed to evaluate the environmental risk and human health risk of heavy metals in some agricultural products cultivated in Dezful and Shushtar in 2020. Materials and Methods: In this research, 18 samples of 1 kg of crops grown on farms in the summer of 2020 were collected randomly from 6 stations in two areas of (Safiabad & Shamsabad farms) and two regions of Shushtar (Gelalak & Shoaibiyeh farms). ICP model Varian 710-ES measured heavy metals. Results: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the literature, numerous studies have found heavy metal contents in various vegetables and fruits, including cucumber, tomato, mustard, cauliflower, cabbage, spinach, carrot, eggplant, red pepper, lettuce, grape, apple, and mango (Amer et al, 2019; Anjum et al, 2021; Bui et al, 2016; Islam et al, 2016; Payandeh et al, 2021; Prabagar et al, 2021; Raja et al, 2015). However, there is limited information on the heavy metal levels of various pickles produced in Turkey or other countries, and there is no research on pickle beverages in this matter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, numerous studies have found heavy metal contents in various vegetables and fruits, including cucumber, tomato, mustard, cauliflower, cabbage, spinach, carrot, eggplant, red pepper, lettuce, grape, apple, and mango (Amer et al, 2019; Anjum et al, 2021; Bui et al, 2016; Islam et al, 2016; Payandeh et al, 2021; Prabagar et al, 2021; Raja et al, 2015). However, there is limited information on the heavy metal levels of various pickles produced in Turkey or other countries, and there is no research on pickle beverages in this matter.…”
Section: Resultsmentioning
confidence: 99%
“…Related vegetables may have been affected by different factors such as soil, irrigation water, industrial activities, and traffic in the environment in which they are grown, or they may have a structure that is more suitable for heavy metal accumulation than others. In the literature, numerous studies have found heavy metal contents in various vegetables and fruits, including cucumber, tomato, mustard, cauliflower, cabbage, spinach, carrot, eggplant, red pepper, lettuce, grape, apple, and mango (Amer et al, 2019;Anjum et al, 2021;Bui et al, 2016;Islam et al, 2016;Payandeh et al, 2021;Prabagar et al, 2021;Raja et al, 2015). However, there is limited information on the heavy metal levels of various pickles produced in Turkey or other countries, and there is no research on pickle beverages in this matter.…”
Section: Heavy Metal Levels Of Pickle Beveragesmentioning
confidence: 99%
“…Day by day, soil ecosystems become a place for harmful substances, scum, waste, and receiving harmful substances, and more than the weather, their pollution burden increases, and on the other hand, more and more Due to the construction of buildings, roads and urban and industrial facilities, a large amount of soil is taken out of the natural circulation and also from the agricultural area and becomes dead soil. Therefore, proper management to have a healthy soil is necessary for human survival [7]. Soils have a special advantage called self-purification and they are considered to be nature's purifiers, but the self-purification power of soil is less than the self-purification power of water and air due to its low exchange with other regions and areas, for this reason soil pollution, It is considered one of the most important types of environmental pollution [8].…”
Section: Introductionmentioning
confidence: 99%